2022
DOI: 10.1002/ca.23884
|View full text |Cite
|
Sign up to set email alerts
|

Trendelenburg (Head‐Down tilt) and head rotation: Ultrasonographic effects on the internal jugular vein for catheterization safety

Abstract: Most guidelines fail to specify patient positioning during central venous catheterization. The objective was to determine the effects of head‐down tilt (Trendelenburg position) and head rotation on the internal jugular vein (IJV). A prospective, observational, longitudinal, and descriptive study using healthy adult volunteers, of both sexes, was performed. The change in position and cross‐sectional areas (CSA) of the right IJV and common carotid artery (CA) were measured by ultrasonography during Trendelenburg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In summarizing this literature, a consistent observation emerges: head rotation leads to occlusion of the IJV on the ipsilateral side, while leaving the contralateral IJV unaffected or possibly more patent. Watson et al (1974) 5 2022) 12 all independently found contralateral IJV diameter, patency, or cross-sectional area to increase following head rotation using ultrasound. Regarding neck flexion, little work has been done to investigate the impacts it may have on IJV occlusion.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…In summarizing this literature, a consistent observation emerges: head rotation leads to occlusion of the IJV on the ipsilateral side, while leaving the contralateral IJV unaffected or possibly more patent. Watson et al (1974) 5 2022) 12 all independently found contralateral IJV diameter, patency, or cross-sectional area to increase following head rotation using ultrasound. Regarding neck flexion, little work has been done to investigate the impacts it may have on IJV occlusion.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…Many studies have identified an increase in IJV CSA with contralateral head rotation, making this a useful maneuver during cannulation [19,49,87,97]. An USG-based study found that the right IJV CSA decreased from 14.2 mm 2 to 8.7 mm 2 when transitioning from a >30° contralateral rotation to <30° ipsilateral rotation [87].…”
Section: Techniques To Reduce Complications and Increase Success Ratementioning
confidence: 99%
“…Increased tilt over 15° increases CSA further but has been shown to increase intracranial pressure [32]. Therefore, IJV cannulation is recommended to be performed at a Trendelenburg position of 5° to 10° with 45° contralateral head rotation, allowing a significant increase in IJV CSA without a significant displacement of the IJV location [49].…”
Section: Techniques To Reduce Complications and Increase Success Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The placement of central venous catheters can be particularly difficult in patients with obesity due to the obscured neck landmarks; furthermore, a high body mass index (BMI) is one of the most significant risk factors for complications during IJV cannulation in the surgical period 5 6. The success rate of central venous cannulation correlates with the venous cross-sectional area (CSA) 7–10. Techniques such as positive end-expiratory pressure, the Trendelenburg position, passive leg raising (PLR): a technique to elevate the patient’s legs to increase the venous return, and the Valsalva manoeuvre have been shown to increase the CSA of the IJV in anaesthetised patients 11–15.…”
Section: Introductionmentioning
confidence: 99%